Powering racial capitalism: Electricity, rate-making, and the uneven energy geographies of Atlanta. (December 2022) - Luke, Nikki
In this paper, I bring together scholarship on racial capitalism and critical energy studies to investigate how electrification contributes to racialized uneven development. I work toward a theory of racialized electricity capital as a state-supported circuit of accumulation through corporate provision of electricity, which is basic need essential to everyday life. I develop a case study of the electrification of Atlanta, Georgia to examine the historical–geographical formation of the relationship between the city's electric utility, Georgia Power, and the state agency that regulates the Company, the Georgia Public Service Commission. I ask how regulation functioned simultaneously to expand and differentiate electricity consumption across Atlanta and in so doing reinforce a racialized labor hierarchy and unequal access to affordable electricity. This case study emphasizes the importance of analyzing the central role of the state in allowing and perpetrating systems of energy provision that create racialized and gendered poverty. Drawing from the most recent hearings regulating electricity rates before the Commission in 2019, I bring to the fore the work of energy equity activists leading a campaign to Fight the Hike who enact demands for racial justice and a democratic energy system.